Lucas Gausss electrostatic Law from (4-11)() /$ ET(r,v) = E0(r) + Ei(r,v) = E0(r)*(1 - λ(v))/(1 - β^2*sin(θ)^2)^(3/2) /*--+ First approach - using Lucas's (4-37) Howell - Lucas's result for 4-37 Er_second_iteration /$ ET(r,v) = E0(r) *(1 + 3/2*β^2*sin(θ)^2 + 15/8*β^4*sin(θ)^4 + 35/16*β^6*sin(θ)^6 + ...) - E0(r)*λ(v)*(1 + 3/2*β^2*sin(θ)^2 + 15/8*β^4*sin(θ)^4 + 35/16*β^6*sin(θ)^6 + ...) /* Using the binomial expansion result of (4-38) : 04_38 Binomial_expansion_for_E0_terms /$ (1 - β^2*sin(θ)^2)^(-3/2) = 1 + 3/2*β^2*sin(θ)^2 + 15/8*β^4*sin(θ)^4 + 35/16*β^6*sin(θ)^6 + ... ET(r,v) = E0(r) *(1 - β^2*sin(θ)^2)^(-3/2) - E0(r)*λ(v)*(1 - β^2*sin(θ)^2)^(-3/2) ET(r,v) = (1 - λ(v))*E0(r)/(1 - β^2*sin(θ)^2)^(3/2) /* so this works well starting with Lucas's (4-37), but the latter may have incorrectly retained the E0*lambda term!? /*----+ Second approach - using Howells (4-37 iteration4 26Jun2016) I did NOT get the same kind of result as Lucas - mine is more like Newtons binomial expansion, than the binomial series that is used in the text. Isaac Newton : /$ (1 - x^2)^(3/2) = 1 - 3/2*x^2 + 3/8*x^4 + 1/16*x^6 ... /* Howell 4th iteration : /$ ET = + E0 *(1 + 3/2*(β*sin(θ))^2 + 3/4 *(β*sin(θ))^4 + 1/4 *(β*sin(θ))^6 + 1/8 *(β*sin(θ))^8 + 3/32 *(β*sin(θ))^10 ) - E0*λ(v)*( + 1/6 *(β*sin(θ))^6 + 1/8 *(β*sin(θ))^8 ) /* 26Jun2016 Further iterations will PERHAPS reduce the value of coefficents beyond the "betaSin^4" term, but it appears that the coefficient of the "betaSin^4" term itself WONT reduce with further iterations (?). Binomial expansion of /$ (1 - (β*sin(θ))^2)^(3/2) /* would give : /% ETods(POIo,t=0) = + E0ods(POIo,t=0)*(1 + 3/2*β*sin(Aθoc(POIo))^2 + 3/8 *β*sin(Aθoc(POIo))^4 - 1/16 *β*sin(Aθoc(POIo))^6 + 3/128*β*sin(Aθoc(POIo))^8 - 3/256*β*sin(Aθoc(POIo))^10 + 7/1024*β*sin(Aθoc(POIo))^12 + ... ) = + E0ods(POIo,t=0)*(1 - 3/2*β^2*sin(Aθpc(POIo(t),t=0))^2)^(3/2) /* I assume that the E0*L(v)* term disappears with iterations, and that Howells 4th iteration is "immature" and probably harbours errors. Therefore, at this time, just take the binomial expansion instead : /% ETods(POIo,t=0) = E0ods(POIo,t=0)*(1 - 3/2*β^2*sin(Aθpc(POIo(t),t=0))^2)^(3/2) = E0ods(POIo,t=0)*(1 + 3/2*β*sin(Aθoc(POIo))^2 + 3/8 *β*sin(Aθoc(POIo))^4 - 1/16 *β*sin(Aθoc(POIo))^6 + 3/128*β*sin(Aθoc(POIo))^8 - 3/256*β*sin(Aθoc(POIo))^10 + 7/1024*β*sin(Aθoc(POIo))^12 + ... ) /*++++++++++++++++++++++++++++++++++++++ /*add_eqn "no_issue 04_39 /* E(r,v) for constant velocity, non-point charge, observer reference frame /$L ET(r,v) = (1 - λ(v))*E0(r)/(1 - β^2*sin(θ)^2)^(3/2) /$H ET(r,v) = (1 - λ(v))*E0(r)/(1 - β^2*sin(θ)^2)^(3/2) /* WARNING : simple using Lucas's (4-37), but is this incorrect? Second approach using Newtons expansion shown as well. In the second approach : (1 - L(v)) does NOT appear!! /% ETods(POIo,t=0) = E0ods(POIo,t=0)*(1 - 3/2*β^2*sin(Aθpc(POIo(t),t=0))^2)^(3/2)